Developing a culture of nursing research in neonatal clinical care in Western Australia - Aydon, L.; Hauck, Yvonne; Murdoch, J.; Foster, C. (Cambridge Publishing, 2014)
Aim: The purpose of our study was to develop a culture of nursing research in neonatal clinical care in Western Australia (WA) by developing a neonatal research agenda. Background: Nursing research provides nurses with evidence for practice, informing them of relevant best practice. Many nurses view their role as providing nursing care but not actually conducting research. However, the evidence to inform nursing care must be provided by nursing-led research. Methods: A three-round Delphi approach was conducted over a nine-month period (April to December 2012) with data collection lasting four weeks for each round. During round one, neonatal nurses were asked to suggest research topics they felt were relevant to nursing within a neonatal clinical area. In round two, nurses were asked to rank 37 topics in six themes from lowest to highest priority. Round three asked the nurses to prioritise the 15 highest ranking topics. Results: The final results were derived from round three after the nurses listed the highest ranking topics from round two. Nurses identified the top two topics as: (1) Medication safety and nurses' confidence to question prescribed orders; and (2) The effect that a series of failed extubations may have on the extremely low birth weight (ELBW) infant. Conclusion: The findings have highlighted research topics considered most important to Western Australian nurses employed in neonatal clinical care. The Delphi approach encourages ownership of the research process which can then be used to foster a culture of nursing research.